2019
DOI: 10.1007/s10711-019-00433-5
|View full text |Cite
|
Sign up to set email alerts
|

Cutoff on hyperbolic surfaces

Abstract: In this paper we study the common distance between points and the behavior of a constant length step discrete random walk on finite area hyperbolic surfaces. We show that if the second smallest eigenvalue of the Laplacian is at least 1/4, then the distances on the surface are highly concentrated around the minimal possible value, and that the discrete random walk exhibits cutoff. This extends the results of Lubetzky and Peres ([20]) from the setting of Ramanujan graphs to the setting of hyperbolic surfaces. By… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Although Iwaniec's theorem has been generalized in various directions [Hux86,Sar87,Hum18], as far as we know, Iwaniec's result has not been directly improved, so speaking about density of eigenvalues, Theorem 1.8 establishes for random covers the best result known in the arithmetic setting for eigenvalues above the Kim-Sarnak bound 975 4096 [Kim03]. Density estimates such as Theorem 1.8 have applications to the cutoff phenomenon on hyperbolic surfaces by work of Golubev and Kamber [GK19].…”
Section: Gafa a Random Cover Of A Compact Hyperbolic Surface 599mentioning
confidence: 99%
“…Although Iwaniec's theorem has been generalized in various directions [Hux86,Sar87,Hum18], as far as we know, Iwaniec's result has not been directly improved, so speaking about density of eigenvalues, Theorem 1.8 establishes for random covers the best result known in the arithmetic setting for eigenvalues above the Kim-Sarnak bound 975 4096 [Kim03]. Density estimates such as Theorem 1.8 have applications to the cutoff phenomenon on hyperbolic surfaces by work of Golubev and Kamber [GK19].…”
Section: Gafa a Random Cover Of A Compact Hyperbolic Surface 599mentioning
confidence: 99%
“…The reason is that the entire continuous spectrum is contained in V 0 ( [42]). For more details for hyperbolic surfaces, see [27].…”
Section: Look Atmentioning
confidence: 99%
“…Recently, Sarnak made a density conjecture which is an approximation to the very naive Ramanujan property and should serve as a replacement of it for applications. Some instances of this general idea were previously given for hyperbolic surfaces ( [52,27]) and for graphs ( [6,35]). Our goal here is to give a general framework for the proof of similar density conjectures and their use in applications.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we mention that in [35] a different direction is taken: replacing PGL 2 (Q p ) with PGL 2 (R), the authors suggest the notion of Ramanujan surfaces, which are hyperbolic Riemann surfaces which spectrally behave like their universal cover, the hyperbolic plane. It is then shown that a discrete random walk with constant-length steps on these surfaces exhibits L 1 -cut-off.…”
Section: Theorem 53 ([34]) Srw On the Vertices Of Ramanujan Complexes Associated With Pglmentioning
confidence: 99%